THE EFFECT OF SELF-EFFICACY, MOTIVATION, AND ENTREPRENEURIAL EDUCATION ON ENTREPRENEURIAL INTEREST FOR PIK-R TEENAGERS IN SURAKARTA – INDONESIA - Arinda, Theofany Bahana Tirta (AIBPM Publisher, 2024)
Entrepreneurs are those who possess sales acumen, ranging from generating concepts to providing tangible products or services. In the realm of economics, the significance of fostering entrepreneurship cannot be overstated. The objective of this study is to examine the impact of self-efficacy, motivation, and entrepreneurship education on the level of interest in entrepreneurship among teens from PIK-R in Tipes Village, Serengan, Surakarta Central Java, Indonesia. This study used a purposive sampling technique, selecting a sample of 41 youths from the overall population. The material used in this study included interviews, questionnaires, and documentation. The study employs interest in entrepreneurship as the dependent variable, while self-efficacy, motivation, and entrepreneurship education are used as the independent factors. The methodology used in this study is multiple linear regression. The findings of the study indicate that there is a partial correlation between motivational self-efficacy and entrepreneurship education, and the level of interest in entrepreneurship among teens from PIK-R in Types Village, Serengan, Surakarta, Central Java, Indonesia